2019
DOI: 10.3389/fphys.2019.00211
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Endurance Running Training Associated With Photobiomodulation on 5-Km Performance and Muscle Soreness: A Randomized Placebo-Controlled Trial

Abstract: This study aimed to investigate the influence of endurance running training associated with PBM on endurance performance variables and muscle soreness in untrained men. Thirty untrained men were distributed randomly into a placebo (PLA) group and photobiomodulation group (PBMG) and they performed 8 weeks of running training. The PBMG had the PBM performed before all training sessions. The PBM was applied using LED equipment with 56 diodes of red light (660 nm) and 48 diodes of infrared light (850 nm). The appl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 33 publications
0
16
0
1
Order By: Relevance
“…Based on an a priori power analysis, using G * Power 3.1 software (Faul et al, 2007 ), we adopted a power of 0.80, α = 0.05, a correlation coefficient of 0.5, a non-sphericity correction of 1, and a strong effect ( f = 0.4) of PBMT on CK and salivary IL-6 concentration. The rationale for the chosen effect size was based on priori power analyses from previous research using smaller 0.25 (Orssatto et al, 2019 ) and larger 0.52 effect sizes with a similar sample size to the current study (Peserico et al, 2019 ). From these values, a sample size of 12 was calculated using guidelines established by Beck ( 2013 ), which produced an actual power of 0.88 for the primary outcomes of CK and salivary IL-6.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on an a priori power analysis, using G * Power 3.1 software (Faul et al, 2007 ), we adopted a power of 0.80, α = 0.05, a correlation coefficient of 0.5, a non-sphericity correction of 1, and a strong effect ( f = 0.4) of PBMT on CK and salivary IL-6 concentration. The rationale for the chosen effect size was based on priori power analyses from previous research using smaller 0.25 (Orssatto et al, 2019 ) and larger 0.52 effect sizes with a similar sample size to the current study (Peserico et al, 2019 ). From these values, a sample size of 12 was calculated using guidelines established by Beck ( 2013 ), which produced an actual power of 0.88 for the primary outcomes of CK and salivary IL-6.…”
Section: Methodsmentioning
confidence: 99%
“…Studies that have examined the effects of PBMT on recovery and performance following exercise protocols include simple open-chain isolated single-joint exercises, such as knee extension (Antonialli et al, 2014 ; Baroni et al, 2015 ; de Paiva et al, 2016 ; De Marchi et al, 2017 ; Rossato et al, 2018 ) and elbow flexion (Larkin-Kaiser et al, 2015 ; Machado et al, 2017 ; Nausheen et al, 2017 ; Rigby and Hagan, 2019 ; Vieira et al, 2019 ). Studies have progressed to more dynamic protocols, such as such as in-game competitions (De Marchi et al, 2019 ; Dornelles et al, 2019 ), sport-specific tests (Pinto et al, 2016 ), running (Malta et al, 2016 , 2018 ; Dellagrana et al, 2018 ; Peserico et al, 2019 ), plyometrics (Fritsch et al, 2016 ), and cycling (Teles et al, 2015 ; Malta et al, 2018 ). In addition, research has examined highly-trained sample populations, such as athletes in jiu-jitsu (Follmer et al, 2018 ), judo (Orssatto et al, 2019 ), volleyball (Ferraresi et al, 2015 ; da Cunha et al, 2019 ; Vieira et al, 2019 ), rugby (Pinto et al, 2016 ), water polo (Zagatto et al, 2016 ), and futsal (De Marchi et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…This lack of effects of laser PBM on RPE and muscle performance in our study and others involving biceps brachii muscle (Higashi et al, 2013) in contrast to the positive effects observed on the quadriceps muscle (Toma et al, 2018) raises the possibility that laser PBM may have different effects on small and large muscles. However, this supposition is not supported by recent studies that have found no positive effect on physical performance and markers of muscle recovery and damage following the PBM irradiation by light-emitting diodes (LEDs) or laser to the larger muscles or the whole body in young adult men (Zagatto et al, 2016(Zagatto et al, , 2020Malta et al, 2018;Peserico et al, 2019;Dutra et al, 2020;Ghigiarelli et al, 2020). Therefore, in light of our findings and that of others, its seems that the lack of positive effect of PBM is more associated with the inherent ineffectiveness of the therapy itself than with other factors, such as the type of irradiation (laser or LED), sex, and irradiated muscle.…”
Section: Discussionmentioning
confidence: 93%
“…due to the slight differences in the predictive power found between these variables and the 5-km running performance time (Figure 1), with the V peak_TF being almost as good as the CS 1 , 2 , 3 and CS 1 , 3 . Nevertheless, previous studies have shown that V peak_T is highly reliable (Peserico et al, 2014) and has been reported to be a valid measure to prescribe and evaluate improvements in the endurance performance of recreational runners (Peserico et al, 2019).…”
Section: Discussionmentioning
confidence: 97%